2018
DOI: 10.1007/s00429-018-1734-x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the cognitive signature of human brain networks derived from structural and functional connectivity

Abstract: Numerous neuroimaging studies have identified various brain networks using task-free analyses. While these networks undoubtedly support higher cognition, their precise functional characteristics are rarely probed directly. The frontal, temporal, and parietal lobes contain the majority of the tertiary association cortex, which are key substrates for higher cognition including executive function, language, memory, and attention. Accordingly, we established the cognitive signature of a set of contrastive brain ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 82 publications
(145 reference statements)
5
24
0
Order By: Relevance
“…The high similarity in the neural networks of RSA and FCA provides support for the idea that brain areas showing similar stimulus-related selectivity are also intrinsically connected. Our finding is in line with previous resting-state fMRI studies that have identified functionally relevant networks, such as the primary visual network, auditory network, motor network, and cognitive networks, during rest (e.g., Biswal et al, 1995;Fox and Raichle, 2007;Jung et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high similarity in the neural networks of RSA and FCA provides support for the idea that brain areas showing similar stimulus-related selectivity are also intrinsically connected. Our finding is in line with previous resting-state fMRI studies that have identified functionally relevant networks, such as the primary visual network, auditory network, motor network, and cognitive networks, during rest (e.g., Biswal et al, 1995;Fox and Raichle, 2007;Jung et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Such distinctions between networks derived from different methods have also been observed in the recent study of Jung and her colleagues (Jung et al, 2018) comparing resting-state fMRI and structural connectivity. Although their comparison involves different methods than ours, they provided some possible explanations that should be considered in the current study.…”
Section: Discussionsupporting
confidence: 62%
“…The high similarity in the 491 neural networks of RSA and FCA provides support for the idea that brain areas showing similar 492 stimulus-related selectivity are also intrinsically connected. Our finding is in line with previous 493 resting-state fMRI studies that have identified functionally relevant networks, such as the 494 primary visual network, auditory network, motor network, and cognitive networks, during rest 495 (e.g., Biswal et al, 1995;Fox and Raichle, 2007;Jung et al, 2018). 496…”
Section: Comparing Network 362supporting
confidence: 86%
“…Such distinctions between the network structures derived from different methods has 523 also been observed in the recent study of Jung and her colleagues (Jung et al, 2018) comparing 524 resting-state fMRI and structural connectivity. Although their comparison involves different 525 methods than ours, they provided some possible explanations that should be considered in the 526 current study.…”
Section: Comparing Network 362mentioning
confidence: 64%
See 1 more Smart Citation